Market dynamics and challenges in the Pineapple value chain in Modhupur, Bangladesh - Hasan, Md Rashidul; Jahan, Khosnur; Moniruzzaman, S M; Afrin, Tanjina (Annals of Bangladesh Agriculture, 2025)
This study was conducted to identify the market actors in the pineapple value chain, and assess profit margins of main market actors along the chain. This research also identified major problems and suggestion to improve pineapple value chain in Tangail district. This study surveyed 60 pineapple market actors by using pre-tested interview schedule. The study found four market actors such as Faria, Aratdar, Bepari and retailer in the study area. The study discovered crucial marketing channels involved in pineapple marketing and main marketing functions performed by the market actors in the study area. Market actors handled a large volume of pineapple by using different transportation modes such as Rickshaw, van, auto van, trolley, trolley van, tractor and truck. Market actors collected market information by market visit, newspaper, mobile phone and fellow traders. Among all the market participants, total cost of marketing for purchasing and selling pineapple was highest for Faria and lowest for retailer. Faria added the largest amount of value among the market participants, at Tk. 1183.34 per 100 kg of pineapple. In the research area, Aratdar had the lowest net margin (Tk. 131.4/100 kg) and retailer had the highest (Tk. 363.88/100 kg). The study also identified the crucial problems facing by the market participants in the pineapple value chain. Additionally, they offered some recommendations for how to enhance the current pineapple value chain in the study area. Ann. Bangladesh Agric. 28(1): 167-179